THE DISOURSE OF GLORIFYING WATER IN THE BALINESE SCRIPTUAL TRADITION TO SUPPORT THE AGRICUTURAL CULTURE AS THE IMPLEMENTATION OF “NANGUN SAD KRTI LOKA BALI” - Suardiana, I Wayan (E-Journal of Cultural Studies, 2023)
This current study is intended to investigate the importance of glorifying water especially in agriculture as explicitly mentioned in the Balinese traditional texts. The data used in the study is the qualitative data obtained using the library research method and the observation, translating, and note-taking techniques. The data was analyzed using the descriptive-analytic method and the inductive technique. The data analysis is presented using the informal method and the narrative technique. The results of analysis show that the glorification of water, as one of the important components of the farming life in Bali, has been explicitly mentioned in the traditional texts. The sustainability and cleanliness of water, as an important component of the life of the living creatures on earth should be maintained. To this end, it is firmly mentioned in the texts of Manawa Dharma?astra , Canakya Nitisastra, Artha ??stra, dan ?arasamuccaya that it is important to make every attempt to maintain the sustainability of water to allow life to last forever. The objective fact in the field shows that the quality of the water used for irrigating the wet rice fields is inadequate as it has been polluted by different types of wastes. Keywords: water, irrigation, strong ideology, polluted